MR angiography follow-up 10 years after cryptogenic nonperimesencephalic subarachnoid hemorrhage - Wenz, Holger; Ehrlich, Gregory Marius; Scharf, Johann; Groden, Christoph; Schmiedek, Peter; Seiz-Rosenhagen, Marcel (PLOS ONE, 2015)
Objectives: Long-term magnetic resonance angiography (MRA) follow-up studies regarding cryptogenic nonperimesencephalic subarachnoid hemorrhage (nSAH) are scarce. This single-centre study identified all patients with angiographically verified cryptogenic nSAH from 1998 to 2007: The two main objectives were to prospectively assess the incidence of de novo aneurysm with 3.0-MRI years after cryptogenic nSAH in patients without evidence for further hemorrhage, and retrospectively assess patient demographics and outcome. Methods: From prospectively maintained report databases all patients with angiographically verified cryptogenic nSAH were identified. 21 of 29 patients received high-resolution 3T-MRI including time-of-flight and contrast-enhanced angiography, 10.2 ± 2.8 years after cryptogenic nSAH. MRA follow-up imaging was compared with initial digital subtraction angiography (DSA) and CT/MRA. Post-hemorrhage images were related to current MRI with reference to persistent lesions resulting from delayed cerebral ischemia (DCI) and post-hemorrhagic siderosis. Patient-based objectives were retrospectively abstracted from clinical databases. Results: 29 patients were identified with cryptogenic nSAH, 17 (59%) were male. Mean age at time of hemorrhage was 52.9 ± 14.4 years (range 4 - 74 years). 21 persons were available for long-term follow-up. In these, there were 213.5 person years of MRI-follow-up. No de novo aneurysm was detected. Mean modified Rankin Scale (mRS) during discharge was 1.28. Post-hemorrhage radiographic vasospasm was found in three patients (10.3%); DCI-related lesions occurred in one patient (3.4%). Five patients (17.2%) needed temporary external ventricular drainage; long-term CSF shunt dependency was necessary only in one patient (3.4%). Initial DSA retrospectively showed a 2 x 2 mm aneurysm of the right distal ICA in one patient, which remained stable. Post-hemorrhage siderosis was detected 8.1 years after the initial bleeding in one patient (4.8%). Conclusion: Patients with cryptogenic nSAH have favourable outcomes and do not exhibit higher risks for de novo aneurysms. Therefore the need for long-term follow up after cryptogenic nSAH is questionable.